Teleconsultation as knowledge management system: Recognizing the issues contributing to its underutilization in hospitals - Ramli R.; Ali N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Health care; Historic preservation; Information use; Knowledge acquisition; Knowledge based systems; Management information systems; Expertise development; Healthcare organizations; Knowledge exchange; Knowledge management system; Medical practitioner; Remote medical care; Technology acceptance; Teleconsultadon; Knowledge management